A APLICABILIDADE DA LEI 10.098/2000 PARA O INGRESSO DE ESTUDANTES DEFICIENTES VISUAIS ÀS UNIVERSIDADES FEDERAIS EM CAMPOS DOS GOYTACAZES/ RJ.BRASIL.2010 - 2015. - Pereira Carneiro, Auner; Gomes da Silva Muylaert Monteiro de Castro, Bianca; Gomes da Silva Muylaert Monteiro de Castro, Bianca (LINKSCIENCEPLACE, 2016)
When talking about accessibility, typically has focused on the disabled, seeking ways as ramps, elevators and wheelchair accessible to supply parameters. When considering the accessibility within educational institutions, more particularly in Universities, thought about accessibility remains the same. Therefore, the aim of this work is to show what should be done for a student with visual impairments, in relation to accessibility in the university context.